Antimicrobial Resistance Patterns and Serological Diversity of Shigella Species from Patient Isolates at University Teaching Hospital in Lusaka, Zambia - Mike Nundwe; Joseph Yamweka Chizimu; John Mwaba; Misheck Shawa; Rodrick S. Katete; Mable Mwale Mutengo; Ruth Nakazwe; Namwiinga R. Mulunda; Cephas Sialubanje; Mox Malama Kalumbi; Yamba Kaunda; Rapheal Chanda; et al. (Bacteria)
Background: Shigella species are the leading cause of human shigellosis. In Zambia, more than 30% of children experiencing diarrhea are infected with Shigella species. The increasing resistance of Shigella species to the recommended therapy is of great concern. Therefore, this study investigated the antibiotic resistance profiles and phenotypic and genotypic characteristics of Shigella isolates at the largest referral hospital in Zambia. Methodology: Of the forty-eight archived presumptive Shigella isolates, thirty-two were serologically confirmed and subjected to antimicrobial susceptibility testing using the Kirby Bauer disk diffusion method. Thereafter, polymerase chain reaction was performed to detect the bla genes. Results: Most isolates were Shigella flexneri (16/32, 50%) and Shigella sonnei (14/32, 44%), while Shigella boydii and Shigella dysenteriae were rare. High resistance rates were noted for sulfamethoxazole/trimethoprim (78%) and tetracycline (75%), while 15.6% of the isolates showed resistance to ciprofloxacin and/or azithromycin. The blaTEM gene encoding beta-lactamase was detected in 7/32 (22%) of isolates. Conclusions: In this study, a significant number of multidrug-resistant isolates were identified. Additionally, Shigella species resistant to the World Health Organization-recommended drugs call for strengthened laboratory diagnosis and close monitoring of these pathogens to guide the clinical management of shigellosis.